Spatial distribution of turbulent mixing in the upper ocean of the South China Sea - Xiao-Dong Shang; Chang-Rong Liang; Gui-Ying Chen (Ocean Science, 2017)
The spatial distribution of the dissipation rate (ε) and diapycnal diffusivity (κ) in the upper ocean of the South China Sea (SCS) is presented from a measurement program conducted from 26 April to 23 May 2010. In the vertical distribution, the dissipation rates below the surface mixed layer were predominantly high in the thermocline where shear and stratification were strong. In the regional distribution, high dissipation rates and diapycnal diffusivities were observed in the region to the west of the Luzon Strait, with an average dissipation rate and diapycnal diffusivity of 8.3 × 10−9 W kg−1 and 2.7 × 10−5 m2 s−1, respectively, almost 1 order of magnitude higher than those in the central and southern SCS. In the region to the west of the Luzon Strait, the water column was characterized by strong shear and weak stratification. Elevated dissipation rates (ε > 10−7 W kg−1) and diapycnal diffusivities (κ > 10−4 m2 s−1), induced by shear instability, occurred in the water column. In the central and southern SCS, the water column was characterized by strong stratification and weak shear and the turbulent mixing was weak. Internal waves and internal tides generated near the Luzon Strait are expected to make a dominant contribution to the strong turbulent mixing and shear in the region to the west of the Luzon Strait. The observed dissipation rates were found to scale positively with the shear and stratification, which were consistent with the MacKinnon–Gregg model used for the continental shelf but different from the Gregg–Henyey scaling used for the open ocean.